Flight status of robotic asteroid sample return mission Hayabusa2. (October 2016) - Tsuda, Yuichi; Nakazawa, Satoru; Kushiki, Kenichi; Yoshikawa, Makoto; Kuninaka, Hitoshi; Watanabe, Seiichiro
Abstract: The Japan Aerospace Exploration Agency launched the asteroid sample return spacecraft "Hayabusa2" on December 3, 2014. Hayabusa2 will reach the C-type asteroid 1999 JU3 in 2018, and return back to the Earth in 2020. Sample collections from three sites, four surface rovers deployment and a 4 MJ-class kinetic impact crater generation are planned in the 1.5 years of the asteroid-proximity operation. The mission objective of Hayabusa2 has three aspects, science, engineering and exploration, all of which would be expanded by the successful round-trip journey. This paper describes the outline of the Hayabusa2 mission and the current flight status after the seven month of the interplanetary cruise.